VALIDATION OF PCR-RFLP TESTING METHOD TO DETECT PORCINE CONTAMINATION IN CHICKEN NUGGET - Tri Joko Raharjo; Winda Cahyaningtyas; Surajiman Surajiman; Istini Istini; Deni Pranowo (Indonesian Journal of Chemistry, 2012)
PCR-RFLP technique to detect porcine contamination in chicken nugget has been developed and validated in this research. Various concentrations of pork were fortified during preparation of the nugget. DNA was then isolated from the nugget followed by PCR employed primers which targeted a 359 bp cytB gene fragment of mitochondrial DNA. For RFLP, the PCR product was digested by means of BamHI and BseDI enzymes. Cutting DNA fragments from nugget containing pork using BseDI enzyme produced DNA fragment with size 228 and 131 bp, while cutting with BamHI enzyme produce DNA fragments with sizes 244 and 115 bp. All of these fragments were not present in RFLP analysis of pork-free nugget. The method shows good specificity and precision and could detect porcine contamination in the nugget up to 5%. The method has been applied to test commercial nugget. Four brand of Halal-labeled commercial nugget as well as four brand of non labeled one gave negative porcine contamination.